2019
DOI: 10.1675/063.042.0204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Culling on Movements and Dispersal Rates of Yellow-Legged Gulls (Larus michahellis) from a Western Mediterranean Colony

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…By contrast, other smaller gulls, such as the Black-legged Kittiwake (Rissa trydactyla), were shown to have much smaller local recruitment rates, ranging between 35 and < 10% (Porter and Coulson 1987;Coulson and Coulson 2008;McKnight et al 2019). Estimates for the Herring Gull (Larus argentatus) have also reported considerably low local recruitment rates (< 40%) (Chabrzyk and Coulson 1976;Parsons and Duncan 1978), though in this case the cull of breeding birds could have promoted philopatry rates values abnormally high (Bosch et al 2000(Bosch et al , 2019. The effect of external factors like culling programs on recruitment is important, and the values from some colonies may not be extrapolated to other colonies since this would lead false premises in demographic models (Brooks and Lebreton 2001).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…By contrast, other smaller gulls, such as the Black-legged Kittiwake (Rissa trydactyla), were shown to have much smaller local recruitment rates, ranging between 35 and < 10% (Porter and Coulson 1987;Coulson and Coulson 2008;McKnight et al 2019). Estimates for the Herring Gull (Larus argentatus) have also reported considerably low local recruitment rates (< 40%) (Chabrzyk and Coulson 1976;Parsons and Duncan 1978), though in this case the cull of breeding birds could have promoted philopatry rates values abnormally high (Bosch et al 2000(Bosch et al , 2019. The effect of external factors like culling programs on recruitment is important, and the values from some colonies may not be extrapolated to other colonies since this would lead false premises in demographic models (Brooks and Lebreton 2001).…”
Section: Discussionmentioning
confidence: 92%
“…If we call this last concept 'local' recruitment, it can be then stated as a synonym of philopatry. The local recruitment among close-by wellestablished colonies has been one of the least known aspects on seabird biology (Gaston 2004), though the body of studies dealing with this subject is increasing (Bosch et al 2019;Davis et al 2019;McKnight et al 2019). The analysis of local recruitment rates in colonial seabirds is called to play a very relevant role in our comprehension of the dynamics and demographic factors driving seabird populations (Spear et al 1998;Cam et al 2002;Payo-Payo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current study highlights the role of immigration in maintaining genetic diversity and allowing population persistence in the face of even extreme and lengthy demographic pressures, further supporting the importance of patch connectivity for both demographic and genetic resilience. Although other studies have demonstrated the ability of immigration to counter high local mortality in populations, including from lethal culling of managed populations [ 69 , 70 ], our study represents an extreme case of severe population reduction (all observed adults removed from the population) occurring long term (over eight consecutive generations), and represents a particularly strong test of the ability of immigration to maintain local populations.…”
Section: Discussionmentioning
confidence: 97%